Merkel cell carcinoma of the head and neck in the south-east of England. Issue 10 (December 2021) - Bowe, C.M.; Bean, T.; Loke, R.; Gallagher, N.; Rooney, J.; Surwald, C.; Dhanda, J.; Moody, A.; Bisase, B.; Norris, P.; Barrett, A.W.; Lachanas, V.; et al.
Abstract: Merkel cell carcinoma (MCC) is a rare and highly aggressive neuroendocrine malignancy of the skin. Its incidence is increasing with half of cases involving the head and neck. To the best of our knowledge, few large studies have been published in the UK, and to date this is the largest reported series of head and neck MCC. We retrospectively reviewed the outcomes of patients with MCC in three hospitals in the south-east of England over a 12-year period (2008–2019). Diagnosis was based on histological data following biopsy. Overall survival and disease-specific survival were calculated using Kaplan–Meier and log-rank tests. Fifty-eight patients met the inclusion criteria (24 stage I, 22 stage II, 9 stage III, and 3 unclassified). Median disease-free survival was 36 months (95% CI 0 to 77.2) and median overall survival 50 months (95% CI 29.9 to 70). Overall five-year survival was 34.4% (95% CI 17% to 52%) with two-year survival at 62% (95% CI 48% to 76%). Five-year disease-free survival was 26.7% (95% CI 17 to 52%) with two-year disease-free survival at 54% (95% CI 40% to 68%). To date, this is the largest UK based study reporting overall and disease-free survival associated with MCC of the head and neck. Half the patients presented late, and surgery was the mainstay of treatment, augmented by adjuvant radiotherapy. There is a need to better stratify patients at risk of developing metastatic disease, with the use of sentinel lymph node biopsy and positron-emission tomography-computed tomography (PET-CT), as immunotherapy and targeted agents are now available to treat advanced disease.